2014
DOI: 10.2967/jnumed.113.132969
|View full text |Cite
|
Sign up to set email alerts
|

Integrin αvβ6–Targeted SPECT Imaging for Pancreatic Cancer Detection

Abstract: Integrin α v β 6 , a member of the integrin family, is specifically expressed in many malignancies but not in normal organs. Overexpression of integrin α v β 6 is usually correlated with malignant potential and poor prognosis. In this study, we describe the synthesis and evaluation of a 99m Tc-labeled integrin α v β 6 -targeting peptide as a SPECT radiotracer for the in vivo imaging of integrin α v β 6 expression. Methods: An integrin α v β 6 -targeting peptide (denoted as the HK peptide) was conjugated with 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 29 publications
0
57
0
Order By: Relevance
“…Such compounds, for example, the linear peptides A20FMDV2 (sequence: NAVPNLRGDLQVLAQKVART, derived from foot-and-mouth disease virus, FMDV) (21), H2009.1 (sequence: RGDLATLRQL) (22), and cyclic peptide S 0 2 (23) were equipped with radiolabels and applied for in vivo imaging of avb6 expression (24) by SPECT (25)(26)(27) and PET (21,(28)(29)(30)(31)(32). More recently, efforts directed at further downsizing and metabolic stabilization of FMDV peptidederived avb6 integrin ligands led to discovery of the cyclic nonapeptide cyclo(FRGDLAFp(NMe)K) (33), which exhibits high avb6 binding affinity (0.26 nM), remarkable selectivity against other integrins (a v b 3 , 632 nM; a5b1, 73 nM; avb5 and aIIbb3, .1 mM), and full stability in human plasma up to 3 h. In addition, its activity was not compromised by functionalization on the lysine side chain, rendering it an optimal starting point for elaboration of molecular probes.…”
mentioning
confidence: 99%
“…Such compounds, for example, the linear peptides A20FMDV2 (sequence: NAVPNLRGDLQVLAQKVART, derived from foot-and-mouth disease virus, FMDV) (21), H2009.1 (sequence: RGDLATLRQL) (22), and cyclic peptide S 0 2 (23) were equipped with radiolabels and applied for in vivo imaging of avb6 expression (24) by SPECT (25)(26)(27) and PET (21,(28)(29)(30)(31)(32). More recently, efforts directed at further downsizing and metabolic stabilization of FMDV peptidederived avb6 integrin ligands led to discovery of the cyclic nonapeptide cyclo(FRGDLAFp(NMe)K) (33), which exhibits high avb6 binding affinity (0.26 nM), remarkable selectivity against other integrins (a v b 3 , 632 nM; a5b1, 73 nM; avb5 and aIIbb3, .1 mM), and full stability in human plasma up to 3 h. In addition, its activity was not compromised by functionalization on the lysine side chain, rendering it an optimal starting point for elaboration of molecular probes.…”
mentioning
confidence: 99%
“…18 F-FDG PET scans and image analysis were performed using a microPET R4 rodent model scanner (Siemens Medical Solutions) as previously described (12,13). Each A549-fLuc tumor-bearing mouse was intravenously injected with 3.7 MBq of 18 F-FDG, and 5-min static PET scans were acquired at 1 h after injection.…”
Section: F-fdg Petmentioning
confidence: 99%
“…2C) demonstrated that 18 F-PR_b was relatively stable in mouse blood plasma, but rapidly metabolized in vivo within 30 min post-injection. The rapid blood clearance and relatively low metabolic stability of 18 F-PR_b, which could be attributed to the linear structure of the peptide as observed for other linear peptide-based radiotracers, 40) possibly compromised the efficient accumulation of the probe in the tumor. That is maybe why the differences in tumor uptake between 18 F-PR_b and its control probe were not as large as the differences in cell-and tissue-bound activities between the two probes obtained from in vitro and ex vivo studies.…”
Section: 39) 18mentioning
confidence: 99%